PERANAN PENYIDIK PEGAWAI NEGERI SIPIL BALAI BESAR PENGAWAS OBAT DAN MAKANAN DALAM MENERTIBKAN PEREDARAN MIE KUNING BASAH YANG MENGANDUNG ZAT BERBAHAYA BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2012 TENTANG PANGAN DI WILAYAH HUKUM KOTA PEKANBARU - Arimbi, Dinda; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Currently, many food products are not suitable for consumption because it contains substances that are harmful to the human body are still free beredar.Zat-harmful substances are not only found on the product label but also on traditional foods, one yellow noodles basah.Produsen fraudulent use of hazardous substances in the processing of wet yellow noodles so the noodles remain resistant and the colors that attract consumers, but this is very detrimental to consumers in terms of health because it can endanger the health of consumers.As for the purpose of this thesis is how the role, barriers, and efforts Civil Servant Investigators Great Hall of the Food and Drug Administration to regulate the circulation of yellow noodles soggy containing hazardous substances based on Law No. 18 Year 2012 on Food in the jurisdiction of the city of Pekanbaru ,The conclusion that can be derived from this study is the first, the role of Civil Servant Investigators Great Hall of the Food and Drug Administration Pekanbaru not the maximum, due to very maze of cases handled by the investigator until today. Second, barriers faced by Civil Servant Investigators Great Hall of the Food and Drug Administration Pekanbaru is influenced by several factors such as law, law enforcement officers factors, factors and factors humans. infrastructure, efforts in overcoming the barriers that do Servant Investigators civil Hall of the Food and Drug Administration Pekanbaru is to add members investigator, enhance the effectiveness of HR in the organization, increasing cooperation with the police, increase the budget for the purpose of investigation and to disseminate to the public. Suggestions author of the issues examined are the First, that Civil Servant Investigators Great Hall of the Food and Drug Administration Pekanbaru can play its role to the fullest. Secondly, in order that Civil Servant Investigators Great Hall Pekanbaru Food and Drug Administration to coordinate with the police, businesses and people in the discipline circulation wet yellow noodles containing berbahaya. Thirdsubstances, are not expected to increase the number of personnel investigator and increase the budget for the purpose of investigation.Keywords: Investigation - Hazardous Substances - Food Products